2021
DOI: 10.1109/access.2021.3052489
|View full text |Cite
|
Sign up to set email alerts
|

Particle Swarm Optimization for Automatically Evolving Convolutional Neural Networks for Image Classification

Abstract: Designing Convolutional Neural Networks from scratch is a time-consuming process that requires specialist expertise. While automated architecture generation algorithms have been proposed, the underlying search strategies generally are computationally expensive. The existing methods also do not explore the search space efficiently, and often lead to sub-optimal solutions. In this research, we propose a novel Particle Swarm Optimization (PSO)-based model for deep architecture generation to address the above chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 47 publications
0
13
0
1
Order By: Relevance
“…Furthermore, the aforementioned A-BiLSTM architecture implemented in this research was shown to be highly effective, but with further experimentation with different layer and hyperparameter settings [24][25][26][27][28][29][30][31][32], additional improvements in performance could be made. Evolutionary algorithms [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] could also be exploited pertaining to the above parameter tuning as well as architecture generation processes. Moreover, it would also be beneficial to employ additional medical audio datasets to further evaluate model efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the aforementioned A-BiLSTM architecture implemented in this research was shown to be highly effective, but with further experimentation with different layer and hyperparameter settings [24][25][26][27][28][29][30][31][32], additional improvements in performance could be made. Evolutionary algorithms [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] could also be exploited pertaining to the above parameter tuning as well as architecture generation processes. Moreover, it would also be beneficial to employ additional medical audio datasets to further evaluate model efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…e convolutional neural network is also widely used in image classification. In order to solve the problem of large parameter space of training network, Lawrence [14] proposed a depth architecture generation model based on particle swarm optimization (PSO). It is used to search space effectively and generate an automatic evolution convolutional neural network to classify images.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, Neuroevolution can find better CNN architectures for a specific task efficiently, allowing researchers without DL experience to find optimum CNN architectures for their fields of study [14], [43]. Neuroevolution has been applied to image classification [14], [31], [43], [44], [45], [46], [47], [48], [49], [50], [51], medical imaging segmentation [52], [53], and human activity recognition [54], among other problems [55], [56], [57], [58], [59], [60], [61].…”
Section: Introductionmentioning
confidence: 99%